Natural Mineral Waters and Metabolic Syndrome: Insights From Obese Male and Female C57BL/6 Mice on Caloric Restriction - Narciso, Laura; Martinelli, Andrea; Torriani, Flavio; Frassanito, Paolo; Bernardini, Roberta; Chiarotti, Flavia; Marianelli, Cinzia (Frontiers in Nutrition, 2022)
Metabolic syndrome (MetS) represents one of the greatest challenges to public health given its serious consequences on cardiovascular diseases and type 2 diabetes. A carbohydrate-restricted, low-fat diet is the current therapy for MetS. Natural mineral waters (NMWs) are known to exert beneficial effects on human health. Our primary objective was to shed light on the potential therapeutic properties of NMWs in MetS. A total of 125 C57BL/6 male and female mice were included in the study. Of these, 10 were left untreated. They were fed a standard diet with tap water throughout the study period, and stayed healthy. The remaining 115 mice were initially fed a high-calorie diet (HCD) consisting of a high-fat feed (60% of energy from fat) with 10% fructose in tap water, served ad libitum over a period of four months to induce MetS (the MetS induction phase). Mice were then randomly divided into six treatment groups and a control group, all of which received a low-calorie diet (LCD), but with a different kind of drinking water, for two months (the treatment phase). Five groups were each treated with a different kind of NMW, one group by alternating the five NMWs, and one group – the control group – was given tap water. Body weight and blood biochemistry were monitored over the six-month trial. After four months, male and female mice on HCD developed obesity, hypercholesterolaemia and hyperglycaemia, although gains in body weight, total cholesterol and blood glucose in males were greater than those observed in females (P< 0.0001). When combined with an LCD, the NMWs rich in sulphate, magnesium and bicarbonate, and the minimally mineralized one were the most effective in reducing the blood levels of total cholesterol, HDL cholesterol, and glucose. Sex differences emerged during both the MetS induction phase and the treatment phase. These results suggest that NMWs rich in specific macronutrients, such as bicarbonate, sulphate and magnesium, and minimally mineralized water, in combination with an LCD, may contribute to controlling blood lipid and glucose levels in subjects with MetS. Further studies are needed to confirm these results and to extend them to humans.